2011
DOI: 10.1016/j.tins.2011.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Slitrks as emerging candidate genes involved in neuropsychiatric disorders

Abstract: Slitrks are a family of structurally-related transmembrane proteins belonging to the leucine-rich repeat (LRR) superfamily. Six family members exist (Slitrk1-Slitrk6), and all are highly expressed in the central nervous system (CNS). Slitrks have been implicated in mediating basic neuronal processes ranging from neurite outgrowth and dendritic elaboration to neuronal survival. Recent studies in humans and genetic mouse models have led to the identification of Slitrks as candidate genes that may be involved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
97
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(98 citation statements)
references
References 119 publications
1
97
0
Order By: Relevance
“…Recently, Slitrk3 was shown to control inhibitory synapse development selectively (13). Despite this progress, little about the synaptic functions of other Slitrk isoforms, apart from their ability to regulate neurite outgrowth (14), has been studied in detail.…”
mentioning
confidence: 99%
“…Recently, Slitrk3 was shown to control inhibitory synapse development selectively (13). Despite this progress, little about the synaptic functions of other Slitrk isoforms, apart from their ability to regulate neurite outgrowth (14), has been studied in detail.…”
mentioning
confidence: 99%
“…Although the function of these genes in mDA neurons remains unknown, these proteins have been shown to affect neurite outgrowth (27) and are involved in the formation of regulation synapses (28). Human genetic studies also have linked rare mutations in SLITRK genes with obsessive-compulsive spectrum disorders and other neuropsychiatric disorders including attention deficit hyperactivity disorder (29). A change in the expression of genes important for the correct wiring or for the synaptogenesis of mDA neurons could indeed have diverse consequences on behavior (including hyperactivity), but further studies would be required to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we showed that mutation of SLITRK6 results in a human syndrome that includes high myopia and sensorineural deafness as the only clinical findings and confirmed a similar phenotype in Slitrk6 mutant mice. SLITRK gene family members are highly expressed in both human and murine central nervous systems (20,21) and are currently considered emerging candidate genes for neuropsychiatric disorders (29). The family consist of 6 structurally related transmembrane proteins belonging to the LRR superfamily and are single-pass (type 1) transmembrane proteins highly expressed in the central nervous system (23).…”
Section: Discussionmentioning
confidence: 99%